Whole‐exome sequencing in adult patients with developmental and epileptic encephalopathy: It is never too late. Issue 5 (1st September 2020) - Minardi, Raffaella; Licchetta, Laura; Baroni, Maria Chiara; Pippucci, Tommaso; Stipa, Carlotta; Mostacci, Barbara; Severi, Giulia; Toni, Francesco; Bergonzini, Luca; Carelli, Valerio; Seri, Marco; Tinuper, Paolo; et al.
Abstract: Developmental and epileptic encephalopathies (DEE) encompass rare, sporadic neurodevelopmental disorders and usually with pediatric onset. As these conditions are characterized by marked clinical and genetic heterogeneity, whole‐exome sequencing (WES) represents the strategy of choice for the molecular diagnosis. While its usefulness is well established in pediatric DEE cohorts, our study is aimed at assessing the WES feasibility in adult DEE patients who experienced a diagnostic odyssey prior to the advent of this technique. We analyzed exomes from 71 unrelated adult DEE patients, consecutively recruited from an Italian cohort for the EPI25 Project. All patients underwent accurate clinical and electrophysiological characterization. An overwhelming percentage (90.1%) had already undergone negative genetic testing. Variants were classified according to the American College of Medical Genetics and Genomics guidelines. WES disclosed 24 (likely) pathogenic variants among 18 patients in epilepsy‐related genes with either autosomal dominant, recessive or X‐linked inheritance. Ten of these were novel. We obtained a diagnostic yield of 25.3%, higher among patients with brain malformations, early‐onset epilepsy and dysmorphisms. Despite a median diagnostic delay of 38.7 years, WES analysis provided the long‐awaited diagnosis for 18 adult patients, which also had an impact on the clinical management of 50% of them. Abstract :